Tindak Tutur Direktif Siswa Kepada Guru dan Teman Sejawat Dalam Pembelajaran Bahasa Arab - Syammary, Naufal Akmal; Syifaussakinah, Syifaussakinah; AlamAlam, Fajar Nur Syah; Firmansyah, Haris Furkon Hasbi (UIN ANTASARI, 2024)
This qualitative study aims to analyze students' speech acts in Arabic language learning using Miles & Huberman techniques of data analysis. The pragmatic approach based on the theory of speech acts of Bach and Harnish with passive participatory observation data collection techniques (passive participation). The data in this study included the directive speech acts employed passive participatory observation data collection techniques. The data in this study includes directive speech acts used by the students include requestives Speech Act used when asking, encouraging, and inviting, questions used when asking, investigating, and invoking, mandates used when giving orders and instructing, prohibitives used when prohibiting and advisories used when suggesting or asking permission.